Aluminum-titanium-boron-zinc-zirconium alloy as well as preparation method and application thereof
By adding trace amounts of zinc and zirconium to the aluminum-titanium boron refiner, the problems of high preparation temperature and high cost of existing refiners are solved, and efficient and uniform refining of aluminum and cost reduction are achieved.
Patent Information
- Application Number
- CN202411657029.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-19
- Publication Date
- 2025-03-04
AI Technical Summary
The existing aluminum-titanium boron refiners are prepared with high temperature and high energy consumption, and rare earth elements need to be added to obtain uniform and fine plasmids, resulting in increased costs.
Use aluminum-titanium boron zinc-zirconium alloy as the refining agent. By adding trace amounts of zinc and zirconium to the aluminum-titanium boron alloy, the operating temperature is reduced and grain refinement is promoted, and rare earth elements are avoided.
It significantly reduces the preparation temperature, improves the grain refinement effect, reduces the amount and cost, and achieves efficient and uniform refinement of aluminum.
Smart Images

Figure CN119553145A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to an aluminum-titanium-boron-zinc-zirconium alloy, a preparation method and application thereof, and belongs to the technical field of aluminum-titanium-boron refiners. Background Art
[0002] Aluminum alloys are increasingly used in aerospace and other technical fields due to their light weight and easy processing. With the development of society, the market's requirements for the quality of aluminum alloy ingots are gradually increasing. As the specifications of some high-strength aluminum alloy ingots increase, they are prone to problems such as coarse grains, resulting in a decrease in overall performance. The commonly used refinement method is to add refiners such as aluminum titanium boron. The addition of refiners increases the nucleation points during the solidification process, thereby refining the grains.
[0003] The existing aluminum-titanium-boron refiner requires a high temperature for preparation, which not only consumes a lot of energy, but also brings great potential risks. In order to obtain more uniformly dispersed fine particles, rare earth elements need to be added, and the amount used is large, which leads to an increase in cost. To this end, the present invention provides an aluminum-titanium-boron-zirconium alloy, which can significantly promote further grain refinement while reducing the preparation temperature, and does not need to add rare earth elements, has low cost and is easy to operate. Summary of the invention
[0004] The invention provides an aluminum-titanium-boron-zinc-zirconium alloy, a preparation method and application thereof, which can be used as an aluminum refiner with low preparation temperature, good refinement effect and small dosage.
[0005] In order to solve the above technical problems, the technical solutions adopted by the present invention are as follows:
[0006] An aluminum-titanium-boron-zinc-zirconium alloy consists of the following components: 3.5-4.5% titanium, 0.6-0.8% boron, 0.01-0.03% zinc, 0.02-0.05% zirconium, unavoidable impurities ≤0.25%, and the balance aluminum.
[0007] The present application adds trace amounts of zinc and zirconium to the aluminum-titanium-boron alloy, which can significantly promote further grain refinement while promoting material flow and reducing operating temperature.
[0008] In aluminum-titanium-boron alloys, the selection of the content of each element is very important, and they match and promote each other. For example, if the content of titanium or boron is changed, the size of TiB2 and TiAi3 particles will be affected. If the content of zinc or zirconium is changed, while the degree of refinement will be affected, the operating temperature will also be affected, and the two promote each other.
[0009] The present invention does not require the addition of rare earth elements, has low cost and is easy to promote industrialization.
[0010] When preparing the aluminum-titanium-boron-zinc-zirconium alloy, the raw materials used include aluminum ingots, zinc ingots, potassium fluorotitanate, potassium fluoroborate and potassium fluorozirconate.
[0011] The purity of the above aluminum ingot is not less than 99.7%.
[0012] The purity of the zinc ingot is not less than 99.9%.
[0013] The % in the present invention, unless otherwise specified, are all mass percentages.
[0014] During preparation, the raw materials are weighed according to the element ratio.
[0015] As one of the specific implementation schemes, the mass ratio of the above-mentioned aluminum ingot, zinc ingot, potassium fluorotitanate, potassium fluoroborate and potassium fluorozirconate is: 1000: (0.1-0.35): (180-250): (72-100): (0.5-2).
[0016] The preparation method of the aluminum-titanium-boron-zinc-zirconium alloy comprises the following steps:
[0017] 1) taking aluminum ingot, zinc ingot, potassium fluorotitanate, potassium fluoroborate and potassium fluorozirconate according to the proportion;
[0018] 2) Melt the aluminum ingot, add the zinc ingot at a temperature of 670-700°C, and after the zinc ingot is completely melted, keep it warm for 10-15 minutes and degas and refine;
[0019] 3) adding a mixture of potassium fluorotitanate, potassium fluoroborate and potassium fluorozirconate to the aluminum liquid obtained in step 2) to react, and after the reaction is completed, pouring out acid water, cleaning slag, and degassing and refining;
[0020] 4) Continuously casting and rolling the aluminum liquid obtained in step 3), during which an electromagnetic stirring device is added to the crystallizer to electromagnetically stir the alloy liquid (obtained in step 3) before crystallization, the electromagnetic stirring frequency is 2-25 Hz, the excitation current is 28-33 A, and the electromagnetic stirring cooling water flow rate is 50-250 m 3 / h.
[0021] In the above step 4), an electromagnetic stirring device is added to the crystallizer to increase the electromagnetic stirring function of the aluminum liquid before crystallization, so that the internal structure of the alloy liquid moves again when it is about to crystallize, which will make the internal structure (TiAl3, TiB2 particles) more evenly distributed and finer.
[0022] Compared with the existing method, the temperature is reduced by more than 50°C, which is a huge contribution to production practice.
[0023] In order to improve the uniformity and fineness of the aluminum-titanium-boron-zinc-zirconium alloy, in step 3), a mixture of potassium fluorotitanate, potassium fluoroborate and potassium fluorozirconate is added twice. After each addition, the mixture is reacted at 750-800°C for 15-20 minutes, the acid water is poured out, and the slag is cleaned.
[0024] Further preferably, in step 3), the mass ratio of the mixture added for the first time (a mixture of potassium fluorotitanate, potassium fluoroborate and potassium fluorozirconate) to the mass ratio of the mixture added for the second time (a mixture of potassium fluorotitanate, potassium fluoroborate and potassium fluorozirconate) is 4:6.
[0025] The above step 3) is carried out under electromagnetic stirring conditions with an excitation current of 280-290A and a frequency of 40-50Hz.
[0026] The above-mentioned aluminum-titanium-boron-zinc-zirconium alloy is used for the refinement of aluminum, and the mass dosage of the aluminum-titanium-boron-zinc-zirconium alloy is 0.2-0.3‰ of the mass of aluminum.
[0027] The technologies not mentioned in the present invention are all referred to the prior art.
[0028] The aluminum-titanium-boron-zinc-zirconium alloy of the present invention has trace amounts of zinc and zirconium added to the aluminum-titanium-boron alloy, which can significantly promote further grain refinement while promoting material flow and reducing operating temperature, making TiAl3 and TiB2 more evenly dispersed and finer; the preparation is simple, and electromagnetic stirring is added before crystallization, so that the internal structure of the alloy liquid moves again when the alloy liquid is about to crystallize, which makes the internal structure (TiAl3, TiB2 particles) more evenly distributed and finer; with a smaller amount of aluminum-titanium-boron-zirconium-zirconium alloy, efficient and uniform refinement of aluminum can be achieved, thereby reducing costs. BRIEF DESCRIPTION OF THE DRAWINGS
[0029] Figure 1 This is a flow chart for preparing the aluminum-titanium-boron-zinc-zirconium alloy of the present invention;
[0030] Figure 2 The internal structure of the aluminum-titanium-boron-zinc-zirconium alloy obtained in Example 1 (metallographic picture);
[0031] Figure 3 This is a particle size distribution diagram of TiAl3 particles of the aluminum-titanium-boron-zinc-zirconium alloy obtained in Example 1 (the unit of the abscissa is μm);
[0032] Figure 4 This is a particle size distribution diagram of TiB2 particles of the aluminum-titanium-boron-zinc-zirconium alloy obtained in Example 1 (the unit of the abscissa is μm);
[0033] Figure 5 Schematic diagram of the grain size (x50) of pure aluminum after being refined using the aluminum-titanium-boron-zinc-zirconium alloy obtained in Example 1. DETAILED DESCRIPTION
[0034] In order to better understand the present invention, the content of the present invention is further explained below in conjunction with the embodiments, but the content of the present invention is not limited to the following embodiments.
[0035] The purity of the aluminum ingot used in each example is 99.7%; the purity of the zinc ingot is 99.995%;
[0036] Example 1
[0037] A method for preparing an aluminum-titanium-boron-zinc-zirconium alloy comprises the following steps:
[0038] 1) The composition of aluminum-titanium-boron-zinc-zirconium alloy is: titanium 4%, boron 0.7%, zinc 0.02%, zirconium 0.03%, aluminum 95% and the balance of inevitable impurities (V is 0, Fe ≤ 0.2% in the impurities). Weigh aluminum ingots, zinc ingots, potassium fluorotitanate, potassium fluoroborate and potassium fluorozirconate according to the mass ratio. The amount of aluminum ingots used in one furnace is 1000kg.
[0039] 2) Melt the aluminum ingot, add the zinc ingot at a temperature of 680°C, and after the zinc ingot is completely melted, keep it warm for 10 minutes and degas and refine (the solvent is blown into the alloy liquid with argon for refining and degassing, the refining time is 22 minutes, the argon pressure is 0.2Mpa, the stirring speed is 350rpm, the stirring temperature is 680°C, and the solvent is a mixture of potassium chloride, magnesium nitrate, sodium chloride and calcium nitrate in a mass ratio of 8:12:2:0.3).
[0040] 3) Under the electromagnetic stirring condition of an excitation current of 280A and a frequency of 45Hz, a mixture of potassium fluorotitanate, potassium fluoroborate and potassium fluorozirconate is added to the aluminum liquid obtained in step 2) twice for reaction. For the first time, 40% of the mixture is added, and the reaction is carried out at 780°C for 15 minutes. The acid water is poured out and the slag is cleaned. For the second time, the remaining 60% of the mixture is added, and the reaction is carried out at 780°C for 15 minutes. The acid water is poured out, the slag is cleaned, and degassing and refining are performed (the solvent is blown into the alloy liquid with argon for refining and degassing. The refining time is 20 minutes, the argon pressure is 0.2Mpa, the stirring speed is 350rpm, the stirring temperature is 780°C, and the solvent is a mixture of potassium chloride, magnesium nitrate, sodium chloride and calcium nitrate in a mass ratio of 8:12:2:0.3).
[0041] 4) The aluminum liquid obtained in step 3) is continuously cast and rolled. During the continuous casting and rolling, an electromagnetic stirring device is added to the crystallizer to electromagnetically stir the alloy liquid (obtained in step 3)) before crystallization. The electromagnetic stirring is turned on while continuous casting and rolling. Every 1.5 tons of alloy liquid is cast for 30 minutes, and the average stirring time for 1 kg of aluminum liquid is 1.2 seconds. Continuous casting and rolling obtains aluminum-titanium-boron-zinc-zirconium alloy wire with a diameter of 9.5 mm, a tensile strength of 163.5 MPa, and an elongation after fracture of 32.5%.
[0042] The parameters in step 4) are set as follows:
[0043]
[0044] The internal structure of the product obtained in this example is as follows Figure 2 As shown. Figure 3 As shown, high-power detection by microscope: any 1cm 2 In the longitudinal section, TiAl3 particles are evenly distributed, with an average size of <9μm and a maximum size of <50μm for a single particle. Figure 4 As shown, TiB2 is evenly distributed and dispersed, with an average size of ≤0.7μm, and no loose TiB2 clumps. The total length of Al2O3 and salt attachments is <600μm; the hydrogen content is controlled at 0.2ml / 100gAl through the hydrogen meter.
[0045] The product obtained in this example was refined into pure aluminum (20000μm), and the addition amount was 0.2kg per ton of pure aluminum. Refining occurred in 5s. After 8 hours, Figure 5 As shown, more than 99% of the grains are less than 90 μm.
[0046] Comparative Example 1
[0047] The composition of the obtained aluminum-titanium-boron-zinc-zirconium alloy wire is: titanium 4%, boron 0.2%, zinc 0.02%, zirconium 0.03%, aluminum 95.5%, and the balance of inevitable impurities (V is 0, Fe≤0.2%). Compared with Example 1, the boron content is reduced by 0.5%, and the aluminum content is increased by 0.5%. The rest is reference to Example 1.
[0048] High magnification detection through microscope: any 1cm 2 The average size of TiAl3 particles in the longitudinal section is 20μm, and the maximum size of a single particle is 120μm. The average size of TiB2 particles is 2μm, and there are 4 loose TiB2 agglomerates smaller than 25μm.
[0049] Comparative Example 2
[0050] The composition of the obtained aluminum-titanium-boron-zinc-zirconium alloy wire is: titanium 5%, boron 0.2%, zinc 0.02%, zirconium 0.03%, aluminum 94.5%, and the balance of inevitable impurities (V is 0, Fe ≤ 0.2% in the impurities). Compared with Example 1, the boron content is reduced by 0.5%, the titanium content is increased by 1%, and the aluminum content is reduced by 0.5%. The rest is referred to Example 1. Through high-power detection under a microscope: any 1cm 2 The average size of TiAl3 particles in the longitudinal section is 20μm, and the maximum size of a single particle is 120μm. The average size of TiB2 particles is 2μm, and there are 6 loose TiB2 agglomerates smaller than 25μm.
[0051] Comparative Example 3
[0052] The composition of the obtained aluminum-titanium-boron-zinc-zirconium alloy wire is: titanium 4%, boron 0.7%, zirconium 0.03%, aluminum 95.02%, and the remainder of inevitable impurities (V is 0 in the impurities, Fe ≤ 0.2%). Compared with Example 1, zinc is omitted. The rest are all referred to Example 1. The operating temperature needs to be increased to above 800°C, otherwise the fluidity and alloy properties cannot meet the use requirements. The temperature of each step is increased to 800°C, and the rest are referred to Example 1. High-power detection by microscope: any 1cm 2 The average size of TiAl3 particles in the longitudinal section is 38μm, and the maximum size of a single particle is 180μm. The average size of TiB2 particles is 3μm, and there are 6 loose TiB2 agglomerates smaller than 50μm.
[0053] Comparative Example 4
[0054] The composition of the obtained aluminum-titanium-boron-zinc-zirconium alloy wire is: titanium 4%, boron 0.7%, zinc 0.02%, aluminum 95.03%, and the remaining inevitable impurities (V is 0, Fe≤0.2% in the impurities). Compared with Example 1, zirconium is omitted. The rest is referred to Example 1. Through high-power detection under a microscope: any 1cm 2 In the longitudinal section, the average size of TiAl3 particles reaches 48μm, and the maximum size of a single particle reaches 200μm. The average size of TiB2 particles reaches 5μm, there are 6 loose TiB2 agglomerates of less than 50μm, and 2 loose TiB2 agglomerates of more than 50μm.
[0055] Comparative Example 5
[0056] The composition of the obtained aluminum-titanium-boron-zinc-zirconium alloy wire is: titanium 4%, boron 0.7%, aluminum 95.05%, and the balance of inevitable impurities (V is 0 in the impurities, Fe ≤ 0.2%). Compared with Example 1, zinc and zirconium are omitted at the same time. The rest are all referred to Example 1. The operating temperature needs to be increased to above 800°C, otherwise the fluidity and alloy performance cannot meet the use requirements. The temperature of each step is increased to 800°C, and the rest are referred to Example 1. High-power detection by microscope: any 1cm 2 The average size of TiAl3 particles in the longitudinal section is 54μm, and the maximum size of a single particle is 220μm. The average size of TiB2 particles is 8μm, there are 8 loose TiB2 agglomerates of less than 50μm, and 3 loose TiB2 agglomerates of more than 50μm.
[0057] Comparative Example 6
[0058] The difference from Example 1 is that the electromagnetic stirring in step 4) is omitted. The rest is the same as Example 1.
[0059] High magnification detection through microscope: any 1cm 2 The average size of TiAl3 particles in the longitudinal section is 14μm, and the maximum size of a single particle is 80μm. The average size of TiB2 particles is 1.1μm, and there are 3 loose TiB2 agglomerates smaller than 25μm.
Claims
1. An aluminum-titanium-boron-zinc-zirconium alloy, characterized in that: It is composed of the following components: titanium 3.5-4.5%, boron 0.6-0.8%, zinc 0.01-0.03%, zirconium 0.02-0.05%, unavoidable impurities ≤ 0.25%, and the balance aluminum.
2. The aluminum-titanium-boron-zinc-zirconium alloy according to claim 1, characterized in that: The raw materials used include aluminum ingots, zinc ingots, potassium fluorotitanate, potassium fluoroborate and potassium fluorozirconate.
3. The aluminum-titanium-boron-zinc-zirconium alloy according to claim 1 or 2, characterized in that: The purity of aluminum ingots is not less than 99.7%.
4. The aluminum-titanium-boron-zinc-zirconium alloy according to claim 1 or 2, characterized in that: The purity of zinc ingot is not less than 99.9%.
5. The aluminum-titanium-boron-zinc-zirconium alloy according to claim 1 or 2, characterized in that: The mass ratio of aluminum ingot, zinc ingot, potassium fluorotitanate, potassium fluoroborate and potassium fluorozirconate is: 1000: (0.1-0.35): (180-250): (72-100): (0.5-2).
6. A method for preparing the aluminum-titanium-boron-zinc-zirconium alloy according to any one of claims 1 to 5, characterized in that: The steps include: 1) taking aluminum ingot, zinc ingot, potassium fluorotitanate, potassium fluoroborate and potassium fluorozirconate according to the proportion; 2) Melt the aluminum ingot, add the zinc ingot at a temperature of 670-700°C, and after the zinc ingot is completely melted, keep it warm for 10-15 minutes and degas and refine; 3) adding a mixture of potassium fluorotitanate, potassium fluoroborate and potassium fluorozirconate to the aluminum liquid obtained in step 2) to react, and after the reaction is completed, pouring out acid water, cleaning slag, and degassing and refining; 4) Continuously casting and rolling the aluminum liquid obtained in step 3), during which an electromagnetic stirring device is added to the crystallizer to electromagnetically stir the alloy liquid before crystallization, the electromagnetic stirring frequency is 2-25 Hz, the excitation current is 28-33 A, and the electromagnetic stirring cooling water flow rate is 50-250 m 3 / h.
7. The method for preparing the aluminum-titanium-boron-zinc-zirconium alloy according to claim 6, characterized in that: In step 3), a mixture of potassium fluorotitanate, potassium fluoroborate and potassium fluorozirconate is added in two portions. After each addition, the mixture is reacted at 750-800° C. for 15-20 min, and the acid water is poured out to clean the residue.
8. The method for preparing the aluminum-titanium-boron-zinc-zirconium alloy according to claim 7, characterized in that: In step 3), the ratio of the mass of the mixture added for the first time to the mass of the mixture added for the second time is 4:
6.
9. The method for preparing the aluminum-titanium-boron-zinc-zirconium alloy according to any one of claims 6 to 8, characterized in that: Step 3) is carried out under electromagnetic stirring conditions with an excitation current of 280-290A and a frequency of 40-50Hz.
10. An application of the aluminum-titanium-boron-zinc-zirconium alloy according to any one of claims 1 to 5, characterized in that: For aluminum refinement, the mass dosage of aluminum-titanium-boron-zinc-zirconium alloy is 0.2-0.3‰ of the aluminum mass.